2022
DOI: 10.2196/35268
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-Time Prompts for Running, Walking, and Performing Strength Exercises in the Built Environment: 4-Week Randomized Feasibility Study

Abstract: Background App-based mobile health exercise interventions can motivate individuals to engage in more physical activity (PA). According to the Fogg Behavior Model, it is important that the individual receive prompts at the right time to be successfully persuaded into PA. These are referred to as just-in-time (JIT) interventions. The Playful Active Urban Living (PAUL) app is among the first to include 2 types of JIT prompts: JIT adaptive reminder messages to initiate a run or walk and JIT strength ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Physical activity-only interventions were also reviewed. A 2022 mHealth study of a smartphone application designed to encourage physical activity was performed to compare usability and enjoyment [46]. A total of 20 participants gave feedback on the system, and results indicated that technical issues when using the application negatively affect use [46].…”
Section: Applications Examining Diet or Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity-only interventions were also reviewed. A 2022 mHealth study of a smartphone application designed to encourage physical activity was performed to compare usability and enjoyment [46]. A total of 20 participants gave feedback on the system, and results indicated that technical issues when using the application negatively affect use [46].…”
Section: Applications Examining Diet or Physical Activitymentioning
confidence: 99%
“…A 2022 mHealth study of a smartphone application designed to encourage physical activity was performed to compare usability and enjoyment [46]. A total of 20 participants gave feedback on the system, and results indicated that technical issues when using the application negatively affect use [46]. A separate study of a Bluetooth-enabled resistance band for enhancing strength reported positive feedback on usability in terms of ease of use, ease of learning, and user satisfaction [56].…”
Section: Applications Examining Diet or Physical Activitymentioning
confidence: 99%
“…A feasibility study of a health application used “just in time” prompts to remind users to initiate runs, walks or strength exercises. With use of prompts users reported increased intrinsic motivation for exercise and increased perceived capability or self-efficacy to exercise ( 90 ). Self-efficacy is closely tied with ability, the final ingredient to the Fogg Behavior Model.…”
Section: Psychological Barriers To Exercise In T2d and Potential Solu...mentioning
confidence: 99%